STARS AND HARDSHIPS OF HISTOLOGY AND EMBRYOLOGY DEPARTMENT DEVELOPMENT - Skibinskaya, T.R.; Sokurenko, L.; Chaіkovsky, Yu.B. (World of Medicine and Biology, 2015)
History of creation of Histology and Embryology Department at O.O. Bogomolets National Medical University are analysed in the article. Factors that influenced formation of scientific direction of Kyiv histological school and development of histology and embryology as independent educational subject in Ukraine are considered. Historical and scientific portraits of histology departments pedagogical stuff of the second half of the 19th century are given.
Keywords: histology and embryology department of O.O. Bogomolets National Medical University; history; scientific directions of the department